Tourism routes and trails : theory and practice - David Ward-Perkins; Christina Beckmann; Jackie Ellis; C.A.B. International (Oxfordshire, United Kingdom : Cabi, 2020)
"Tourism Routes and Trails plunges into the world of 'extended' tourism, offering an exploration of the 'routes' phenomenon whereby tourism is no longer for a given destination, but extends over multiple sites, a territory or landscape. Covering how such routes are created, often as ways of clustering experiences, it also reviews their effects on tourism businesses, local populations and other stakeholders. Emphasising the critical role of local communities, volunteers and small businesses, as well as those who provide strategic direction and funding, the book: - Is based in tourism theory, but focuses on the models and practice of route formation; - Includes a rich selection of contemporary examples and cases, showing the reader best practice as well as illustrating challenges and risks; - Covers both strategic issues of concern to nations, regions and local authorities, and the complex dynamics occurring on the ground, such as the role of grass-roots organisations and local communities. Routes allow destinations to diversify their offer and spread the economic and social benefits of tourism. With tourist behaviour increasingly shifting to thematic experiences, this book shows how to create these in a way that is both meaningful for visitors and beneficial for the destination. Suitable for tourism policy makers, economic development agencies and local stakeholders, it is also a vital resource for the next generation; students of tourism, sociology, local politics and economic development"-- Provided by publisher
Keywords: Cultural values; Management; History; Cultural values